Site-specific near-infrared fluorescent labelling of proteins on cysteine residues with meso-chloro-substituted heptamethine cyanine dyes. Issue 45 (9th November 2018) - Canovas, Coline; Bellaye, Pierre-Simon; Moreau, Mathieu; Romieu, Anthony; Denat, Franck; Goncalves, Victor
Abstract : meso -Chloroheptamethine cyanine dyes react selectively with cysteine residues in proteins to give site-specifically labelled NIR fluorescent bioconjugates. Abstract : Near-infrared (NIR) fluorescence imaging is a promising new medical imaging modality. Associated with a targeting molecule, NIR fluorophores can accumulate selectively in tissues of interest and become valuable tools for the diagnosis and therapy of various pathologies. To facilitate the design of targeted NIR imaging agents, it is important to identify simple and affordable fluorescent probes, allowing rapid labelling of biovectors such as proteins, ideally in a site-specific manner. Here, we demonstrate that heptamethine cyanine based fluorophores, such as IR-783, that contain a chloro-cyclohexyl moiety within their polymethine chain can react selectively, at neutral pH, with cysteine residues in proteins to give stable, site-specifically labelled conjugates, that emit in the NIR spectral window. This reaction is exemplified with the labelling of peptides and two protein models: albumin and a Fab′ antibody fragment. The resulting fluorescent proteins are stable and suitable for in vivo NIR imaging applications, as shown on a mice model. This straightforward one-step procedure, that does not require the prior derivatisation of the fluorophore with a bioconjugatable handle, should facilitate the production and use of near-infrared labelled proteins in life sciences.